Penanaman Nilai Nilai Pendidikan Islam melalui Pembelajaran Matematika - Salafudin Tarmudi (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2019)
This research is focused on the strategy of planting the values ​​of Islamic education and the values ​​of Islamic education that can be embedded in mathematics learning. This type of research is library research. The planting of the values ​​of Islamic education in schools, especially non-religious schools, tends to not be resolved properly which has implications for the gap between religious understanding of the community and expected behavior of the community. One thing that can be done is to instill the values ​​of Islamic education through general learning, one of them is mathematics. Planting the values ​​of Islamic education with the process of learning mathematics requires strategies, approaches, methods and techniques. The conclusion in this study is that the values ​​of Islamic education can be embedded using transinternal strategies, integral approaches, reflective methods and clarification and internalization techniques. This is in accordance with what was stated by Abdussakir that the planting of the values ​​of Islamic education in mathematics learning can be done through the integration of mathematics with the Qur'an, which includes four models of integration namely: mathematics from the Qur'an, mathematics for Al Qur'an, mathematics to Qur'an and mathematics with Al Qur'an. In addition, the value of discipline, order and consistency; value of justice; tawakal value; honesty value; social values ​​like giving and avoiding debt and charity and generosity